APPROACHES TO IMPROVING THE FINANCIAL SUPPORT OF REPRODUCTION OF FIXED ASSETS OF PRYLUTSK BAKERY - CHEREP, O.; PRYKHODKO, V. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Nowadays, financial support for the reproduction of fixed assets plays an important and crucial role, which affects the state of the economy. Undoubtedly, for the normal functioning of the enterprise, of course, requires the availability of many specific tools and sources. Namely, such fixed assets, which consist of buildings, structures, machines, tools and other means of labor involved in the production process, are the most important basis of the enterprise. Therefore, the rational and economic use of fixed assets is a priority for the company. Regardless of the form of ownership, for any enterprise fixed assets are the technical and material basis for the production process. The article stipulates that fixed assets are depreciated at any enterprise. The stages of calculation of indicators on improvement of financial maintenance of reproduction of fixed assets of the production enterprise are investigated. Such stages of calculation are: calculation of the technical condition of fixed assets of the enterprise, analysis of the movement of fixed assets, ie the introduction of new technical means to improve the performance of fixed assets at the enterprise. Factor analysis was performed on the basis of formulas: return on assets, capital intensity, capital adequacy and profitability. It is concluded that the reproduction of fixed assets is improved in order to improve the activity at the appropriate level. Key words: technical condition, suitability ratio, renewal of fixed assets, return on capital, capital intensity, capital adequacy, profitability, growth rate.